25.8k views
5 votes
Last question XD

Please answer asap!
3x - 5y = 10
6x + 3y = -6

Marybeth is going to solve this problem by multiplying the top equation by -2. If she does this and combines the equations, what does she get?
A) -13y = -26
B) -7y = 14
C) -2y = 4
D) 13y = -26

User Asaveljevs
by
5.1k points

1 Answer

2 votes

Answer:

The answer to your question is letter D.

Explanation:

3x - 5y = 10 --------- (1)

6x + 3y = -6 ---------- (2)

Following directions

-2( 3x - 5y = 10)

6x + 3y = -6

Expanding

-6x + 10y = -20

6x + 3y = -6

Simplifying

0 + 13y = -26

13y = -26

y = -26/ 13

y = -2

User Mrbox
by
5.6k points